If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 9 + -3 = 13x + -4 Reorder the terms: 9 + -3 + 14x = 13x + -4 Combine like terms: 9 + -3 = 6 6 + 14x = 13x + -4 Reorder the terms: 6 + 14x = -4 + 13x Solving 6 + 14x = -4 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 6 + 14x + -13x = -4 + 13x + -13x Combine like terms: 14x + -13x = 1x 6 + 1x = -4 + 13x + -13x Combine like terms: 13x + -13x = 0 6 + 1x = -4 + 0 6 + 1x = -4 Add '-6' to each side of the equation. 6 + -6 + 1x = -4 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = -4 + -6 1x = -4 + -6 Combine like terms: -4 + -6 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| 4(c+7)=4(c-5) | | r(r-7)=8 | | 12a^2+17a-40=0 | | y=-2x^2+4x-1 | | -5x-17=-97 | | 50-4x=7x+17 | | x(3x+15)=0 | | -20+y=21 | | .66x=45 | | 84-4x=32x+24 | | 3X+6X= | | 5-3(4)= | | 4=3t-6 | | -143-7x=9x+17 | | 5-3X= | | 6x+13=13-7x | | 7z+3=15 | | 132-6x=2x+20 | | -43-2x=13-9x | | -17=x+5 | | 10x+8-5= | | 4x=227 | | 2x^2-9x-17=0 | | x^2+25x-16=0 | | 11y+9=42 | | -2x-1=13 | | 6u=-23 | | x^4+11x^2+10=0 | | 160+7.5h= | | 9m+m-6(m+4m)= | | 7.5h+160= | | 2x+25=47 |